2011
DOI: 10.1243/09544062jmes2319
|View full text |Cite
|
Sign up to set email alerts
|

A novel continuum model for the reduction of numerical errors of finite-element analysis

Abstract: The authors developed a novel numerical formulation that reduces the computational expense of solving linear and non-linear constitutive models. A finite-element constitutive law followed by a novel continuum model is discussed. The proposed approach is employed to reduce numerical errors obtained from the standard finite-element method. The continuum model is based on the Lagrange multipliers strategy along with the finite-difference method and a least-square algorithm. It is crucial to this approach that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The closed form of the equilibrium equation and the equation of compatibility disregarding body force is written as such 12,13 Here, s xx , s yy , and t xy are the stress values obtained from the coarse mesh FE models applied to an arbitrary body shape. Let's define the elevated valves as ŝ xx , ŝ yy , and t xy which are comparable with results obtained from fine mesh FE models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The closed form of the equilibrium equation and the equation of compatibility disregarding body force is written as such 12,13 Here, s xx , s yy , and t xy are the stress values obtained from the coarse mesh FE models applied to an arbitrary body shape. Let's define the elevated valves as ŝ xx , ŝ yy , and t xy which are comparable with results obtained from fine mesh FE models.…”
Section: Methodsmentioning
confidence: 99%
“…The closed form of the equilibrium equation and the equation of compatibility disregarding body force is written as such 12,13…”
Section: Methodsmentioning
confidence: 99%
“…It is unclear whether predictive biomodelling using 3D CT through finite element analysis (FEA) may give a contribute to the identification of patients who should undergo to double transcatheter valve therapy (10,11,17,(88)(89)(90)(91)(92). Some investigators found evidences that a wrinkle process can induced tear in the mitral valve leaflet tissue leading for a progression of diseased MV in presence of degenerative MV disease (93,94) or the EROA may not change after successful TAVR (95).…”
Section: Areas Of Uncertaintymentioning
confidence: 99%